Competition, Corporate Governance, and Regulation in Central Asia : Uzbekistan's Structural Reform Challenges - Broadman, G. Harry (The World Bank, 1999)
May 2000 - Like many Central Asian republics, Uzbekistan has adopted a gradual, cautious approach in its transition to a market economy. It has had some success attaining macroeconomic stability, but microeconomic reforms have lagged behind. It is time to accelerate structural reform. In Uzbekistan state enterprises are being changed into shareholding companies, and private enterprises account for 45 percent of all registered firms. But business decisions to set prices, output, and investment are often not market-based, nor wholly within the purview of businesses, especially those in commercial manufacturing and services. Lines of authority for corporate governance - from state enterprises to private enterprises - are ill-defined, so there is little discipline on corporate performance and little separation between government and business. Nascent frameworks have been created for competition policy (for firms in the commercial sector) and regulatory policy (governing utilities in the infrastructure monopoly sector). But implementation and enforcement have been hampered by old-style instruments (such as price controls) rooted in central planning, by lack of a strong independent regulatory rule-making authority, by the limited understanding of the basic concepts of competition and regulatory reform, and by weak institutional capabilities for analyzing market structure and business performance. Based on fieldwork in Uzbekistan, Broadman recommends: · Deepening senior policy officials' understanding of, and appreciation of the benefits from, enterprise competition and how it affects economic growth. · Reforming competition policy institutions and legal frameworks in line with the country's goal of strengthening structural reforms and improving macroeconomic policy.